The short form of CheA couples chemoreception to CheA phosphorylation. - Wolfe, A J (1994)
Escherichia coli cells express two forms of the chemotaxis-associated CheA protein, CheAL and CheAS, as the result of translational initiation at two distinct in-frame initiation sites in the gene cheA. The long form, CheAL, plays a crucial role in chemotactic signal transduction. As a histidine protein kinase, it first autophosphorylates at amino acid His-48; then, it phosphorylates two other chemotaxis proteins, CheY and CheB. The short form, CheAS, lacks the amino-terminal 97 amino acids of CheAL and, therefore, does not contain the site of autophosphorylation. However, it does retain a functional kinase domain. As a consequence, CheAS can mediate transphosphorylation of kinase-deficient CheAL variants. Here we demonstrate in vitro that CheAS also can mediate transphosphorylation of a CheAL variant that lacks the C-terminal segment, a portion of the protein which is thought to interact with CheW and the chemoreceptors. The presence of CheW and the chemoreceptor Tsr enhances this activity and results in modulation of the transphosphorylation rate in response to the Tsr ligand, L-serine. Because CheAS can mediate this activity, it can restore chemotactic ability to Escherichia coli cells that express this truncated CheAL variant.